2022
DOI: 10.1088/2057-1976/aca9d4
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3D-printed universal oral stent for tongue immobilization in head and neck radiotherapy

Abstract: The primary treatment for head and neck cancer is radiotherapy, which can cause complications and effects, such as the ability to speak, taste, produce saliva, and swallow. An oral stent is an immobilization tool for minimizing the dose in the tongue (or hard palate) by locking the tongue position during radiation delivery. It can improve the treatment accuracy due to less uncertainty caused by tongue position uncertainty between treatment fractions. However, commercial oral stents are not widely adopted in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In recent years, many literatures have studied the mechanism, prevention and nursing intervention of oral toxicity in patients with head and neck tumors during radiotherapy 12–17 . Wearing oral stent during radiotherapy is an important measure to reduce oral tissues radiation dose to reduce oral toxicity 18–25 . When wearing an oral stent, the patient's mouth opens to separate the upper and lower jaw, and the tongue and part of the oral mucosa can be fixed as far away from the high dose area as possible, so as to reduce the oral dose and the occurrence of adverse reactions such as oral mucositis and taste dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many literatures have studied the mechanism, prevention and nursing intervention of oral toxicity in patients with head and neck tumors during radiotherapy 12–17 . Wearing oral stent during radiotherapy is an important measure to reduce oral tissues radiation dose to reduce oral toxicity 18–25 . When wearing an oral stent, the patient's mouth opens to separate the upper and lower jaw, and the tongue and part of the oral mucosa can be fixed as far away from the high dose area as possible, so as to reduce the oral dose and the occurrence of adverse reactions such as oral mucositis and taste dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Wearing oral stent during radiotherapy is an important measure to reduce oral tissues radiation dose to reduce oral toxicity. [18][19][20][21][22][23][24][25] When wearing an oral stent, the patient's mouth opens to separate the upper and lower jaw, and the tongue and part of the oral mucosa can be fixed as far away from the high dose area as possible, so as to reduce the oral dose and the occurrence of adverse reactions such as oral mucositis and taste dysfunction. However, the literature reports are mainly on malignant tumors in the oral cavity (OC), nasal cavity and paranasal sinuses, there are few reports on the wearing of oral devices in patients with NPC during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, it was reported that the use of positioning stent to reduce the irradiation dose to the palate resulted in a reduction of radiation-induced oral mucositis on the palate [10]. Several three-dimensional (3D) printed customized tongue devices were suggested to take the patient-specific structures into account, and dosimetric efficacies were also reported [6][7][8][9][12][13][14][15][16]. In 2022, the interfractional head-up and-down motions in the thermoplastic mask with and without 3D printed tongue-positioning devices were investigated using magnetic resonance imaging [14].…”
Section: Introductionmentioning
confidence: 99%